Comparative assessment of natural and synthetic reproductive inhibitors in Oreochromis niloticus - Jamal, Rafia; Asad, Farkhanda; Naz, Shabana; Hussain, Syed Makhdoom (International Journal of Agricultural and Biological Engineering, 2024)
Nowadays, natural sources of sex reversal agents are preferred over synthetic ones in fish farming due to their reliability and economic value. This study compared the effectiveness of 17α-methyltestosterone (MT), Carica papaya seed meal (PSM) and common carp testes (CCT) with that of tilapia (Oreochromis niloticus) in terms of sex reversal, hematological parameters, gonadal histology, enzymatic activity and overall growth. A 90 d trial was conducted with 560 tilapia fry (2-3 days old) distributed into one control and six treatment aquaria, each with two replicates. Fries were fed with a control diet (T0) or six experimental diets (T1-T6) containing different MT, PSM or CCT levels for 30 d, followed by the control diet for 60 d. MT induced the highest male proportion (85% and 75% in T2 and T1, respectively), while PSM and CCT enhanced tilapia’s growth and carcass composition. Histological analysis revealed gonadal deformities in MT and PSM treatments, which might lead to sterility. The gonadosomatic index (GSI) was reduced in natural treatments than in synthetic ones. Hematological parameters did not show any adverse effects of PSM and CCT. Protease and amylase activities were higher in PSM and CCT than in MT, indicating better digestion and feed absorption. PSM and CCT are biodegradable, locally available and eco-friendly alternatives to synthetic hormones to change sex in tilapia. Natural (plant and animal by products) sources are preferable over synthetic sources as they are less expensive and control prolific breeding in tilapia. Keywords: sex reversal, natural reproductive inhibitors, synthetic reproductive inhibitors, Oreochromis niloticus, Carica papayaDOI: 10.25165/j.ijabe.20241705.9008Citation: Jamal R, Asad F, Naz S, Hussain S M. Comparative assessment of natural and synthetic reproductive inhibitors in Oreochromis niloticus. Int J Agric & Biol Eng, 2024; 17(5): 284-292.